The Appraisal of Commitment in Organizational Environments- Differentiating Organizational Commitment from Employee Satisfaction (European Journal of Interdisciplinary Studies, 2016)
In order to acquire (and maintain) a high degree of commitment of a company’s staff certain conditions must be met both general – that are valid for most organizations focused on profit - and specific - depending on the particularities of each company. Commitment is very relevant in calibrating the business strategy of companies in order to develop employees but also as a central objective for change management. At a general level, building commitment is conditioned on communication with employees on effective leadership, a high degree of satisfaction and a low degree of resistance to change. Change management theorists suggest that any kind of change - both planned and critical incident related- will have negative implications on organizational commitment. Becker considers communication as one of the main factors that affect commitment, important in the growth and continuation. Communication also has implications for organizational culture calibration, transmission of messages via multiple channels and is affected by several factors including commitment (Keyton, 2010). The main difference between commitment and satisfaction is strongly related to the emotional and affective study dimensions of Meyer and Allen’s model on commitment (Keyton, 2010); although satisfaction can generate certain reactions from employees, it has a wide range of meanings from which results can be reported. Commitment may have different affective values because of the implications that it generates and because of their complexity. Accuracy is the most important feature as it helps in measuring commitment and maintaining a high degree of objectivity in data interpretation. Measuring attitudes in social sciences is a subject often problematic because the instruments used do not meet the criteria of validity - do not measure what needs to be measured. Therefore, the measurements may be inaccurate without the use of an appropriate methodology for identifying the exact coefficients of the survey indicators.